2019
DOI: 10.3389/fnut.2019.00125
|View full text |Cite
|
Sign up to set email alerts
|

Hazelnut as Ingredient in Dairy Sheep Diet: Effect on Sensory and Volatile Profile of Cheese

Abstract: The opportunity of replacing expensive feedstuffs with agro-industrial by-products in the diet of food producing animals is raising increasing interest while addressing global concern for the scarcity of natural resources and environmental impact of livestock farming. Hazelnut peels, rich in fiber and vitamins and characterized by a high concentration of fats, is considered a suitable ingredient to be included in the diet of ruminants. The aim of this research was to assess the effect of dietary hazelnut peels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…The HS used in this trial showed a proximate composition very similar to that described in the available published literature [17,26]. In accordance with the results of these authors, the major component in HS was fiber (>500 g/kg DM).…”
Section: Chemical Composition Of Hazelnut Skinsupporting
confidence: 88%
See 3 more Smart Citations
“…The HS used in this trial showed a proximate composition very similar to that described in the available published literature [17,26]. In accordance with the results of these authors, the major component in HS was fiber (>500 g/kg DM).…”
Section: Chemical Composition Of Hazelnut Skinsupporting
confidence: 88%
“…The EE content was also high, falling within the ranges (109.9 to 287.8 g/kg DM) reported by Zeppa et al [17] for four different cultivars. The CP content of HS was low, being comparable to values reported by Cetinkaya and Kuleyin [25] (around 60 g/kg DM) and slightly lower than the values found by Caccamo et al [26] and Longato et al [20] (74 to 79 g/kg DM). Campione et al [27] also reported that around the 68% of protein in HS is in the form of unavailable nitrogen (acid detergent insoluble protein).…”
Section: Chemical Composition Of Hazelnut Skinsupporting
confidence: 81%
See 2 more Smart Citations
“…To our knowledge, no study has evaluated the suitability of this by-product as feedstuffs for ruminants. Only our recent paper investigated the sensory and volatile profile of cheese produced with milk from sheep fed HS [12], but the effect on milk yield and quality was not investigated.…”
Section: Introductionmentioning
confidence: 99%